Heart rate variability: a practical review for the beginner - MIRESCU, Ștefan-Claudiu; CIOCOIU, Andreea Loredana; DAVID, Leontin; TARBA, Corneliu (Studia Universitatis Babeș-Bolyai Biologia, 2017)
Heart rate variability (HRV) refers to beat-to-beat interval changes on the electrocardiogram (ECG) and is considered a noninvasive measure of the autonomic balance. Although classical ECG is a well-known and standardized clinical method, HRV developed abruptly due to the evolution of computerized data acquisition systems in cardiology (digital electrocardiographs) and their software programs. HRV can be evaluated by visual methods (the beat-to-beat tachogram, the histogram and the Poincaré diagram) or by statistically computed parameters. Its applications include sympathovagal balance evaluation, monitoring of different neuropathies and contribution to survival prediction after cardiac acute events. Studies state that HRV can also be used as a method for rapid screening of some autonomic and cardiac diseases, along with other diagnostic procedures.